The Roles of the EBPP Model and of Bio-Medical Approaches in Psychodynamic Therapy - Skean, Karen Riggs (Pragmatic Case Studies in Psychotherapy, 2005)
Goodheart (2005) and Miller (2005) provide important additional dimensions to psychodynamic case studies like mine (Skean, 2005a). Goodheart argues persuasively for making such case studies more publicly accountable by more clearly connecting them to the principles of APA’s recently finalized Evidence-Based Practice in Psychology (EBPP) model. This includes the use of more formalized and standardized measures of therapy process and outcome, including the DSM categories of the American Psychiatric Association, and the use of explicit strategies for minimizing the distortions of cognitive biases and improving judgment. Miller, on the other hand, critiques the use of the DSM and other bio-medical approaches, such as psychopharmacology. I respond to both sets of important ideas, delineating areas of agreement and disagreement with the aim of encouraging other psychodynamic practitioners to address them openly and constructively.